Irrigation Management Transfer: A New Methodology to Improve thePerformance of Agency Managed Irrigation Systems (AMISs) - Singh, Achyut Man (Hydro Nepal: Journal of Water, Energy and Environment, 2009)
This paper presents a new concept on the management of Agency Managed Irrigation Systems with the joint participation of the agency and the users, with their defined roles and responsibilities. The message of the system governance and operation methodology are disseminated to the grass root level of the users. Resource management and water charge collection are anticipated to be firmly applied in the system. The users and Water User's Association and also Department of Irrigation field staff will be well trained in the Irrigation Management Transfer process with capacity building. For sustainability, monitoring and evaluation with independent auditing are part of the process. The general Irrigation Management Transfer procedures adopted by Department of Irrigation are redefined to this new concept in the World Bank assisted Irrigation and Water Resources Management Project. Key words: Irrigation management transfer, water users, AMIS, World Bank, Nepal doi: 10.3126/hn.v3i0.1916 Hydro Nepal Journal of Water, Energy and Environment Issue No. 3, July 2008. Page: 29-34